INTERNALISASI MISOGINI: KEKERASAN SEKSUAL SEBAGAI SENJATA PERANG - Hanryana, Umanitya Fitri; Putri, LG. Saraswati (Paradigma: Jurnal Kajian Budaya, 2025)
This study examines the role of internalized misogyny in sexual violence used as a weapon of war. Misogyny in patriarchal cultures fosters hatred towards women, facilitating sexual violence in armed conflicts. Cases in the Congo, Rwanda, Ukraine, and Yugoslavia demonstrate how sexual violence is systematically employed to demean and destroy women. Through a feminist critical approach and qualitative analysis, this research reveals that sexual violence in war is often not recognized as a weapon of war due to the inferior position of women in patriarchal societies, being merely seen as ordinary crimes despite being systematic and structured human rights violations. Findings indicate that women in war experience layered violence based on their gender, ethnicity, and nationality. Internalized misogyny normalizes sexual violence in war. Therefore, feminist-oriented laws and policies are required to acknowledge women's human rights as part of human rights and provide justice for victims of sexual violence. This study underscores the importance of feminist education to eradicate misogyny and patriarchal cultures. Furthermore, recognition and rehabilitation of sexual violence victims in war zones are necessary to restore affected communities. The author hopes future research will delve deeper to break the impunity in human rights violations and keep the memory of victims and the struggle for justice alive.